Epitope Characterization of an Aromatase Monoclonal Antibody Suitable for the Assessment of Intratumoral Aromatase Activity - Hong, Yanyan (Public Library of Science, 2009)
Immunohistochemistry is one of the most suitable methods for the detection of intratumoral aromatase in order to identify patients who may respond to aromatase inhibitor therapy in hormone-dependent breast cancer. Previous studies showed statistically significant correlation between results of immnuohistochemistry and biochemical analysis in carcinoma components stained by aromatase monoclonal antibody 677. In this study, determination of the antigenic peptides recognized by aromatase antibodies through epitope mapping, combined with the new knowledge on aromatase-reductase interaction, provide insights for understanding various immunostaining patterns using different aromatase antibodies. Our studies on aromatase-reductase interaction also provided critical information on how aromatase and reductase interact with each other on the endoplasmic reticulum membrane, and identified key residues, including K108 of aromatase, that are involved in the interaction with reductase. Through epitope mapping and taking into consideration the interference with aromatase immunohistochemical staining by NADPH-cytochrome P450 reductase, we demonstrated that monoclonal antibody 677 is a suitable antibody for an assessment of intratumoral aromatase activity in breast cancer patients for making clinical management decisions. These results also provide valuable information to identify new aromatase antibodies for immunohistochemical diagnosis of hormone-dependent breast cancer in future.